ANALISIS EVALUASI APLIKASI (SITI NGADU) SISTEM TERPADU PENANGANAN PENGADUAN BERBASIS WEBSITE DI KANTOR IMIGRASI KELAS I TPI BANDUNG - Apriansyah, M.Rizky; Karunia, Ferdyan Samuel; Hilmy, Muhadzib Rezki; Berlian, Theresya (TEMATICS: Technology Management and Informatics Research Journals, 2024)
Abstract. The SITI NGADU application is a web-based integrated system developed by the Class I Immigration Office TPI Bandung to improve the efficiency and quality of public services in handling community complaints. This study aims to evaluate the implementation of the application, particularly from the perspective of technology acceptance using the Technology Acceptance Model (TAM) framework. The findings indicate that the SITI NGADU application significantly enhances the speed and accuracy of handling complaints and simplifies digital archive management. However, the main challenges include low employee understanding of the application's features, limited technological literacy, and inadequate responsive technical support. To address these challenges, it is recommended to conduct intensive training, improve technological literacy, and enhance technical support. Therefore, the SITI NGADU application is expected to be implemented more optimally, supporting the enhancement of immigration services that are more efficient, transparent, and responsive to public needs.